2016
DOI: 10.1111/dth.12391
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity and antibiotic resistance in Propionibacterium acnes isolates and its therapeutic implications: blurring the lines between commensal and pathogenic phylotypes

Abstract: Acne vulgaris is a multifactorial skin disease associated with the colonization of Propionibacterium acnes. Antibiotics are a mainstay of treatment for acne, yet the emergence of resistance against the currently approved antibiotics is a serious concern. In this case report, a slow responder had multiple Propionibacterium acnes isolates with varied levels of sensitivity to the conventional antibiotics. The bacterial isolates obtained from acne samples collected from the patient were analyzed for phylogeny, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…68 Focusing on the molecular mechanism involved in this resistance, the authors further demonstrated that most of the clinical strains belonged to phylotype IA1 38 . In a recent case report, 69 bacterial isolates from a slow responder to antimicrobial treatments were found to be phylogenetically heterogeneous and presented variable resistance to clindamycin. In a surprising manner the pathogenic phylotype IA1 displayed clindamycin sensitivity, whereas phylotype IB, associated with commensals, exhibited high clindamycin resistance.…”
Section: Acnes Response To Antibioticsmentioning
confidence: 99%
“…68 Focusing on the molecular mechanism involved in this resistance, the authors further demonstrated that most of the clinical strains belonged to phylotype IA1 38 . In a recent case report, 69 bacterial isolates from a slow responder to antimicrobial treatments were found to be phylogenetically heterogeneous and presented variable resistance to clindamycin. In a surprising manner the pathogenic phylotype IA1 displayed clindamycin sensitivity, whereas phylotype IB, associated with commensals, exhibited high clindamycin resistance.…”
Section: Acnes Response To Antibioticsmentioning
confidence: 99%
“…In this study, dead P. acnes was used to induce inflammation in both in vitro and in vivo models to evaluate The position of mutation in the nucleotide residue (Escherichia coli numbering) of 23S ribosomal RNA is mentioned in parentheses. A2058G mutation is associated with higher degree of clindamycin resistance, whereas A2059G mutation confers clindamycin susceptibility (Sadhasivam et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Next, we tested VCD-004 using a library of P. acnes clinical isolates with a diverse resistance spectrum to clindamycin and erythromycin (Sadhasivam et al, 2016). These isolates had mutations either in A2058G or A2059G (Escherichia coli numbering) in bacterial 23S peptidyl ribosomal RNA that conferred resistance or susceptibility to clindamycin, respectively.…”
Section: Rational Design and Synthesis Of Vcd Antibioticsmentioning
confidence: 99%
“…A2058 (E. coli numbering) residue is one of the pivotal nucleotides for lincosamide binding at the bacterial target [51]. Point mutation at A2058G in 23S rRNA is reported to confer high clindamycin resistance [52]. Similarly, many reports indicate instances of ermX gene-mediated clindamycin and erythromycin resistance in C. acnes [24].…”
Section: Discussionmentioning
confidence: 99%